Limitations of Charge Transfer State Parameterization Using Photovoltaic External Quantum Efficiency. Issue 41 (22nd September 2020) - Armin, Ardalan; Zarrabi, Nasim; Sandberg, Oskar J.; Kaiser, Christina; Zeiske, Stefan; Li, Wei; Meredith, Paul
Abstract: Free carrier photogeneration in bulk‐heterojunction solar cells composed of blends of acceptor and donor organic semiconductors proceeds via intermolecular charge transfer (CT) states. Non‐adiabatic Marcus theory has proven valid to explain the absorption and emission of these sub‐gap states which have extremely weak emission probabilities and absorption cross sections making them difficult to probe directly using optical spectroscopy. Therefore, the CT state parameters involved in the Marcus model are often extracted from fittings on the photovoltaic external quantum efficiency ( EQE PV ) and electroluminescence. These two spectra are (ideally) interrelated via the so‐called reciprocity principle. In this paper, the limitations of such an approach are demonstrated, in particular the impact of simple low finesse cavity interference effects acting as an uneven spectral filter for emission and absorption. This can produce almost spurious CT state parameterization with, for example, relative errors as large as 90% in absorption coefficients obtained from EQE PV . It is shown how these limitations can be partially lifted using an iterative transfer matrix approach applied to the EQE PV . Abstract : Charge transfer state parameterization based upon external quantum efficiency and electroluminescent is influenced by cavity effects yielding arbitrary results. This is shown to be due to the thickness dependent cavity in(out)put coupling. A practical approach is presented to overcome this issue. The effect is demonstrated in several organic solar cells including non‐fullerene‐based devices.